A 10-Year Personal History of the Radiological Operations Support Specialist - Irwin, William (Health physics (1958), 2025)
The Radiological Operations Support Specialist Program accomplished one of the hardest outcomes-to build and sustain an all-volunteer organization from a few people to hundreds. Even more, the organization created a cadre of newly certified technical specialists able to help the local, state, and federal authorities respond better to a radiological or nuclear catastrophe so our nation can recover faster. The effort has had the endorsement of the United States Congress and the support of three important federal agencies and the national partnership for radiation protection, the Conference of Radiation Control Program Directors. The development of the Radiological Operations Support Specialist (ROSS) occurred over the same time when numerous other references, tools, trainings, and exercises were ushered in. A 10-year period that may be the most remarkable unified radiological emergency preparedness effort yet undertaken. This article describes the key motivators and many of the guidance documents and technical tools and capabilities that came together over the last 10 years that helped build not just an organization of radiological and nuclear emergency response and recovery subject matter experts that the nation needs, but also nearly everything to sustain them effectively for decades to come.